Deli Tobacco as a Cultural Heritage - Rafiqi Rafiqi; Marsella Marsella (Budapest International Research and Critics University, 2021)
Deli tobacco plantation is the first plantation in Tanah Deli. The history of plantations in East Sumatra began with the success of Jacobus Nienhuys planting Deli tobacco in Tanah Deli. Since World War II in 1945, Deli tobacco production has begun to decline. Such a condition has affected the area of Deli tobacco plantations. Since Deli tobacco is an ever triumphed characteristic and pioneer at the international level, tobacco plantations in East Sumatra should be protected and maintained as a cultural heritage. Problems are formulated into how social factors influence the decline of tobacco products and how to protect the landscape of Deli tobacco plantations. This study employed normative juridical research using descriptive analysis. The findings show that the factors influencing the decline production of tobacco among others are decreasing land fertility and difficulty of obtaining a new estate, the global economic depression, the nationalization and the occurrence of social revolutions leading to land grabbing by the community. Deli tobacco is classified as a cultural heritage, a legacy, and a historical landmark of Tanah Deli. Protection of Deli tobacco landscape according to Law No. 11 of 2010 concerning Cultural Heritage states that its existence needs to be preserved due to its important value for history, education, and culture. Conclusion Sustainable landscapes help fulfill the principles of sustainable development as laid out in development goals. The suggestion of the results of this study is that Deli tobacco must be protected and maintained as an agrotourism landscape.